Effect of disinfectant solutions on a denture base acrylic resin. - Carvalho, Cristiane F; Vanderlei, Aleska D; Marocho, Susana M Salazar; Pereira, Sarina M B; Nogueira, Lafayette; Paes-Júnior, Tarcisio J Arruda (My University, 2012)
The aim of this study was to evaluate the hardness, roughness and mass loss of an acrylic denture base resin after in vitro exposure to four disinfectant solutions. Forty specimens (Clássico, Brazil) were prepared and randomly assigned to 4 groups n = 10) according to the disinfectant solution: G1: control, stored in distilled water at 37 degrees C; G2: 1% sodium hypochlorite; G3: 2% glutaraldehyde; G4: 4% chlorhexidine. G2 to G4 were immersed for 60 minutes in the disinfectant solution. Measurements were carried out both before and after immersion in the solution. The surface was analyzed with a surface roughness tester (Surfcorder SE 1700 KOZAKALAB), a microdurometer FM-700 (Future Tech) and a scanning electron microscope (DSM 962-ZEISS). Loss of mass was determined with a digital weighing scale. After disinfection procedures, values were analyzed statistically. The acrylic denture base resin may be vulnerable to surface changes after in vitro immersion in the disinfectant solutions studied.
Keywords: acrylic acid resin; disinfectant agent; denture base; instrument sterilization; solution and solubility; Acrylic Resins; Denture Bases; Disinfectants; Solutions; Sterilization